Comparing Educational Outcomes of Online Module-Based Technology with and without Simulation on Attitudes Toward Care of the Dying in Second Semester BSN Students. Issue 4 (October 2019) - Lewis-Pierre, LaToya; McKay, Mary; Sanko, Jill; Gattamorta, Karina; Azaiza, Khitam
Background: Opportunities to provide competent and compassionate End-of Life (EOL) care to patients and families are limited for nursing students. Method: A mixed methods approach was used to explore the students' attitudes towards caring for an EOL patient in two groups: an on-line-module only group and an on-line module plus simulation group. Results: Statistically significant effect of time was found across the two conditions (F [1, 69] = 7.83, p = .007), indicating that scores on the FATCOD-B significantly improved regardless of the condition over time. The qualitative responses indicated that the simulation experience was more impactful than the on-line module. Conclusions: Innovative education modalities described in the study may assist in preparing the future workforce for the myriad of demands related to health, life, and death.